The Legal Review of the Implementation of the Community Development and Empowerment Program in the Mining Sector - Badrunsyah, Badrunsyah; Muhammad Rusdi, Andi (Journal of Comprehensive Science, 2024)
The Community Development and Empowerment Program (PPM) in the mining sector is a legal obligation imposed on companies to contribute to local community welfare. This obligation is part of the broader corporate social responsibility (CSR) framework, regulated by various laws in Indonesia, such as Law No. 3 of 2020 on Mineral and Coal Mining and Ministerial Regulation of Energy and Mineral Resources No. 1824 K/30/MEM/2018. Despite clear regulations, the effective implementation of PPM remains a challenge, especially regarding law enforcement and community involvement. This study aims to explore and analyze the legal aspects of the implementation of PPM in the mining sector, focusing on how well companies comply with the existing legal framework and what challenges they face in fulfilling their social obligations. The research employs a qualitative approach using a literature review method, analyzing legal texts, academic articles, and regulatory documents related to PPM. The study focuses on understanding the regulatory environment and its application by mining companies. The findings reveal that although the legal provisions governing PPM are comprehensive, there are significant gaps in the monitoring and enforcement of these regulations. Many companies struggle with compliance, and the impact on community development is often limited due to inadequate oversight and community engagement. The study concludes that for the PPM program to be more effective, improvements in legal oversight and the enforcement mechanism are necessary. Additionally, greater efforts are needed to ensure that the PPM benefits are more closely aligned with community needs and that companies are held accountable for their social responsibilities.